Optimization of Barlat 3 parameter material model with aluminum alloy experimental curves - Diosdado De la Peña, José Angel; Prieto Juárez, Marco Antonio; Fuentes Castañeda, Pilar; Méndez Bautista, Hugo; Limon Leyva, Pablo Alberto (Acta Universitaria, 2016)
This paper presents computed constants of 3 parameter Barlat material model, hardening coefficient (n), strength coefficient (K) and anisotropic constants (r00, r45, and r90) obtained from tensile test data for sheet type specimens at different rolling direction (0°, 45°, and 90°). These anisotropic parameters from an aluminum alloy sheet are used to feed three parameter Barlat material model in LS-DYNA® software, to generate a file that is required to perform an optimization in LS-OPT® software. Experimental data is used to generate real strain-real stress curves, and are compared with those obtained from LS-DYNA® simulations with optimized parameters, getting a closer curve to experimental data, particularly in plastic zone.
Keywords: Array; Array; Array; Array; Array